Developing Policies and Mechanisms to Prevent Sexual Harassment in Nepali Higher Education Institutes (International Journal of Multidisciplinary Perspectives in Higher Education, 2025)
Despite sexual harassment being rampant in higher education institutes (HEI) of Nepal, there are no sexual harassment prevention policies or mechanisms in universities. The Government of Nepal formulated the Sexual Harassment at Workplace (Prevention) Act 2014., but it is insufficient in the context of universities. Moreover, due to the lack of policies and mechanisms in place, decisions regarding complaints against sexual harassment are made by those in charge, men in most cases, on an ad-hoc basis. This research paper is based on the literature review of the existing policies on sexual harassment prevention in HEI in Nepal. Based on the review, the paper also provides some strategies for recommendations and outlooks to prevent sexual harassment in higher education institutions in Nepal.